Nocturnal foraging lifts time constraints in winter for migratory geese but hardly speeds up fueling. (25th March 2021) - Lameris, Thomas K; Dokter, Adriaan M; van der Jeugd, Henk P; Bouten, Willem; Koster, Jasper; Sand, Stefan H H; Westerduin, Coen; Nolet, Bart A
Abstract: Climate warming advances the optimal timing of breeding for many animals. For migrants to start breeding earlier, a concurrent advancement of migration is required, including premigratory fueling of energy reserves. We investigate whether barnacle geese are time constrained during premigratory fueling and whether there is potential to advance or shorten the fueling period to allow an earlier migratory departure. We equipped barnacle geese with GPS trackers and accelerometers to remotely record birds' behavior, from which we calculated time budgets. We examined how time spent foraging was affected by the available time (during daylight and moonlit nights) and thermoregulation costs. We used an energetic model to assess onset and rates of fueling and whether geese can further advance fueling by extending foraging time. We show that, during winter, when facing higher thermoregulation costs, geese consistently foraged at night, especially during moonlit nights, in order to balance their energy budgets. In spring, birds made use of the increasing day length and gained body stores by foraging longer during the day, but birds stopped foraging extensively during the night. Our model indicates that, by continuing nighttime foraging throughout spring, geese may have some leeway to advance and increase fueling rate, potentially reaching departure body mass 4 days earlier. In light of rapid climatic changes on the breeding grounds, whether this advancement can be realized and whether it will be sufficient to prevent phenological mismatches remains to be determined. Abstract : While geese are considered diurnal animals, accelerometers reveal that geese graze during moonlit nights in winter to maintain body weight. With the lengthening of days in spring, geese are able to fuel body stores by grazing only during the day and forego nighttime grazing. We use a model to show how much faster the geese might be able to deposit fuel stores needed for migration if they would also graze at night in spring.